Prediction of shaft resistance of bored pile in limestone formation - Chew, Siow Jin (2012)
Piles socketed into limestone are commonly used in Malaysia especially for deep foundation of high rise building at Kuala Lumpur area. The heavy structural loads are transmitted to the bedrock through the contact surface between concrete and the limestone. However much uncertainty involved in the selection of appropriate design procedures for the piles in limestone. Several analytical and empirical methods have been used to evaluate the shaft resistance of piles from three sites located at Kuala Lumpur limestone area. The data of instrumented static load tests were collected for verification purpose. Comparison and analysis were carried out to select the most appropriate method in determining the shaft resistance of rock. Design methodologies by empirical methods that commonly used in Malaysia adopted working rock socket friction based on the rock quality and subject to minimum 5% of rock strength and concrete strength. Some other empirical approaches encounter the strength of intact rock and nature of discontinuities in rock mass to predict the unit shaft resistance in limestone. The other analytical method by modifies friction reduction factor with respect to various rock socket roughness and rock intact strength. The study shows that the predicted skin frictions are highly dependent on unconfined compressive strength and rock quality designation. Findings indicate that Tan (2009) and Salgado (1998) methods well predicted the shaft friction for qu more than 60MPa. By comparing both Salgado (1998) and Tan (2009) methods, it is found that Tan (2009) method is more appropriate for the bored pile design in Kuala Lumpur limestone as it can provide reasonable predictions of shaft resistance all range of rock quality designation whereby Salgado (1998) method required well establish interpretation of the coefficient of weakness of rocks from the rock coring sample.